Analise de índices de produção e reprodução em rebanhos leiteiros canadenses segundo perfil sorológico para diarreia viral bovina e leucose enzootica bovina. - Luciano Bastos Lopes (2007)
Dairy industry comes in recent years passing for significant changes. The agribusiness comes suffering a process from modernization with the adoption of an efficient model of management becoming more competitive to each year. As consequence, efficiency in the whole production process, more than what never, it necessary for the success of the exploration in all the sectors of dairy industry. However, intensive management can influence the prevalence of some pathogenic microorganisms in dairy farms. Some infectious diseases are potentially capable to compromise the viability of a economically sustainable production. This work had as objective to evaluate the interference of the Enzootic Leucosis and BVDV in the milk production, reproduction, culling rates and the economic impact of these deseases in herds from four Canadian provinces. Generalized models of regression for evaluation of epidemiological factors in the data base had been used. The results in this study had demonstrated an multifactorial aspect linked to viruses capabilities to produce losses in dairy farms.